2005
DOI: 10.1063/1.1875751
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of III-nitride blue and ultraviolet light-emitting diodes

Abstract: Polarization-resolved electroluminescence studies of III-nitride blue and ultraviolet (UV) light-emitting diodes (LEDs) were performed. The LEDs were fabricated on nitride materials grown by metalorganic chemical vapor deposition on sapphire substrates (0001). Transverse electric (TE) polarization dominates in the InGaN∕GaN quantum-well (QW) blue LEDs (λ′=458nm), whereas transverse magnetic (TM) polarization is dominant in the AlInGaN QW UV LEDs (λ=333nm). For the case of edge emission in blue LEDs, a ratio (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…8 Experimental anisotropic optical polarization for the luminescence of the m-and c-plane InGaN, GaN, AlGaN, and AlN have been reported. [9][10][11][12][13][14][15][16][17][18] Recently, anisotropic optical polarization has also been discovered in the c-plane AlGaN multiple quantum well ͑MQW͒ laser. 19 In this letter, we report extremely weak surface emission and anisotropic emission from a ͑0001͒ c-plane Al x Ga 1−x N ͑x = 0.66-0.76͒ MQW in the spectral region from 228 to 240 nm under optical pumping, although a definite intensity of edge emission was still observed from the ͑1-100͒ cleaved m-plane facet.…”
mentioning
confidence: 99%
“…8 Experimental anisotropic optical polarization for the luminescence of the m-and c-plane InGaN, GaN, AlGaN, and AlN have been reported. [9][10][11][12][13][14][15][16][17][18] Recently, anisotropic optical polarization has also been discovered in the c-plane AlGaN multiple quantum well ͑MQW͒ laser. 19 In this letter, we report extremely weak surface emission and anisotropic emission from a ͑0001͒ c-plane Al x Ga 1−x N ͑x = 0.66-0.76͒ MQW in the spectral region from 228 to 240 nm under optical pumping, although a definite intensity of edge emission was still observed from the ͑1-100͒ cleaved m-plane facet.…”
mentioning
confidence: 99%
“…3 The polarized EL from InGaN / GaN quantum-well ͑QW͒ LEDs fabricated on a nonpolar plane has been explained by the same origin. 12 On contrary, there are reports that no peak shift has been observed between two polarizations on GaN / AlGaN QW, 13 InGaN / GaN QW, 14 and AlInGaN QW. 14 Emission was assigned to transition from conduction band ͑C͒ to the topmost valence subband.…”
Section: Introductionmentioning
confidence: 79%
“…The observed polarization ratio has been reported to be as high as 7:1 for GaN/InGaN QWs [18]. For common GaN LED structures grown along the c axis, access to this polarized light can only be gained by measurements taken from the edge of the sample [19][20]. Several authors have reported polarized light emission for LED structures grown on nonpolar or semipolar GaN substrates [21][22].…”
Section: Polarized Light Emission Properties Of Gan-based Photonic Crmentioning
confidence: 99%